Dampak Musim Libur Covid-19 Belajar dari Rumah Terhadap Psikologi Anak Sekolah Dasar - Andi Suhandi; Issaura Sherly Pamela (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2020)
This study aims to determine the impact of holidays while studying from home due to the covid 19 pandemic on the psychology of elementary school children. This research was conducted at Hello Kurnia Housing, Sungai Duren Village, Jambi Luar Kota. This research uses a qualitative approach. The type of research in this study is phenomenology with 15 research subjects. this research data is obtained by direct observation an in-depth interviews. The data will be analyzed using the Miles and Huberman model with three steps of analysis, data reduction, display data, and a conclusion. The result of the study show that due to the ongoing covid 19 pandemic, school has become a long holiday and this causes psychological problems for children. children become lazy to study independently at home because they feel lonely, because usually when they are at school children can study together with their teacher and friends. the pandemic causes children to study independenly in their own homes. children become stressed easily. Children often change their feelings depending on the state of their own hearts. Based on the result of this study, it is suggested that paerent in the Hello Kurnia Housing, Sungai Duren Village, Jambi Luar Kota, must be more patient with their children at home during long holidays, so that the child’s psycology is not distrubed. Encourage children to play and are invited to regularly study at home to generate enthusiasm in children. This is so that children remain enthuasiastic about learning in the midst of the covid 19 pandemic.